Listen, Marxist! - Vodovnik, Žiga (Teorija in praksa, 2019)
In this article, we argue that self-management should not be understood as simply an economic project, but as a political form based on the transformation of the core principles of modern capitalist societies. We build on the supposition that self-management does not imply the economic, but primarily the political recomposition of society and that it is therefore necessary to draw attention to economic reductionism in discussions on selfmanagement. The purpose of this article is three-fold: first, we recuperate the original meaning of self-management, its forgotten, anarchist (pre)history. Here we elaborate on anarchist theory of organisation that has dynamised the idea/practice of self-management throughout history. Second, we analyse Yugoslav self-management through categories and the concepts of praxis of philosophy that leads us to conclude that the Yugoslav self-management model was above all a non-political form that remains within the liberal democratic theory framework. Finally, we explore the global massassembly movement Occupy where we consider the recent academic attention paid to the notion of non-state spaces. We analyse the encampments and occupied squares as self-managed exilic spaces in which protesters (in) voluntarily escaped from both state regulation and capitalist accumulation.
Keywords: Anarchism; Anarhizem; Democracy; Demokracija; New social movement; Nova družbena gibanja; praxis; Samoupravljanje; Self-management by employees